Mineralogy and geochemistry of the newly discovered Late Mesozoic granite-pegmatite and associated Sn-Nb-Ta-Be mineralization in the Miao'ershan-Yuechengling composite batholith, northern Guangxi, South China. (1st April 2020) - Tian, Ennong; Wang, Rucheng; Xie, Lei; Zhang, Wenlan; Che, Xudong; Zhang, Rongqing
Graphical abstract: Highlights: Albite granite and pegmatite (aplite) in the Gedongping district are related to Sn–Nb–Ta–Be mineralization. Typical rare-metal minerals in Gedongping granitic rocks include cassiterite, Nb-Ta oxide minerals and beryl. A Late Mesozoic intrusive phase occurred within the composite batholith. Sn-Nb-Ta and W mineralization events were related to magmatic and hydrothermal processes, respectively. Abstract: The Miao'ershan–Yuechengling granitic batholith (MYGB) in the west Nanling Range, South China, contains multiple intrusive phases including the Paleozoic porphyritic biotite granite and Early Mesozoic two-mica and muscovite granite associated with the W–Cu–U mineralization. In this study, the Gedongping granitic rocks, in the central part of the MYGB are shown to be related to Sn–Nb–Ta–Be mineralization. They comprise albite granite, pegmatite, and aplite, and intrude the Paleozoic granite. Sn–Nb–Ta oxide minerals such as cassiterite, columbite-group minerals, microlite and wodginite are common. Beryl occurs in the pegmatite and aplite. Zircon U-Pb isotopic data yielded an age of 153 ± 3 Ma for the formation of the aplite. In situ U-Pb dating of cassiterite from the albite granite and aplite yielded ages of 147 ± 5 and 155 ± 3 Ma, respectively, for the Sn mineralization. Geochemically, theses granitic rocks are rich in SiO2 (~72 wt%), Al2 O3 (~15 wt%), and total alkali (~10 wt%), and the alumina saturation index is 1.0 to 1.1. Combined with the high HfO2 contents (up to 15.1 wt%) and low Zr/Hf ratios (6–35) in zircons, it is indicated that the Gedongping granitic rocks are highly evolved. We infer that the Gedongping granitic rocks underwent magmatic fractionation and subsolidus hydrothermal alteration, based on the textural and compositional variations of the Sn–Nb–Ta oxide minerals. Two fine-grained granite stocks within the MYGB, which were described as Late Mesozoic products, have been confirmed to form during the Paleozoic (420–426 Ma).